Contrast enhanced X-ray computed tomography imaging of amyloid plaques in Alzheimer disease rat model on lab based micro CT system - Kavkova, Michaela; Zikmund, Tomas; Kala, Annu; Salplachta, Jakub; Proskauer Pena, Stephanie L; Kaiser, Josef; Jezek, Karel (Scientific reports, 2021)
Amyloid plaques are small (~ 50 μm), highly-dense aggregates of amyloid beta (Aβ) protein in brain tissue, supposed to play a key role in pathogenesis of Alzheimer's disease (AD). Plaques´ in vivo detection, spatial distribution and quantitative characterization could be an essential marker in diagnostics and evaluation of AD progress. However, current imaging methods in clinics possess substantial limits in sensitivity towards Aβ plaques to play a considerable role in AD screening. Contrast enhanced X-ray micro computed tomography (micro CT) is an emerging highly sensitive imaging technique capable of high resolution visualization of rodent brain. In this study we show the absorption based contrast enhanced X-ray micro CT imaging is viable method for detection and 3D analysis of Aβ plaques in transgenic rodent models of Alzheimer's disease. Using iodine contrasted brain tissue isolated from the Tg-F344-AD rat model we show the micro CT imaging is capable of precise imaging of Aβ plaques, making possible to further analyze various aspects of their 3D spatial distribution and other properties.
Keywords: Animals; vylepšení rentgenového snímku; Female; Radiographic Image Enhancement; biologické markery; Amyloid beta-Peptides; zobrazování trojrozměrné; Biomarkers; Imaging, Three-Dimensional; ženské pohlaví; amyloidní beta-protein; rentgenová mikrotomografie; mozek; počítačové zpracování obrazu; modely nemocí na zvířatech; amyloidní plaky; kontrastní látky; Brain; Alzheimer Disease; Plaque, Amyloid; Disease Models, Animal; krysa rodu Rattus; Alzheimerova nemoc; zvířata; X-Ray Microtomography; Contrast Media; Rats; Image Processing, Computer-Assisted